Faktor Yang Mempengaruhi Nilai Perusahaan Pada Perusahaan Manufaktur - Kenny Howard, Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this study was to analyze the effect of liquidity, profitability, firm size and leverage on firm value on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The research used 54 companies that were selected using purposive sampling method in three years. Data processing technique using multiple regression analysis with SPSS version 22 and Microsoft Excel 2016. The result of this study indicate that liquidity does not significantly influence on firm value, profitability have positive and significantly influence on firm value, firm size have positive and significantly influence on firm value and leverage have positive and significantly influence on firm value. The implication of this study is the need to increase the profitability, firm size and leverage to increase the firm value which will bring a good signal for investors.